Penerapan Pola Pendidikan Israel Menurut Kitab Taurat Bagi Pak Masa Kini - Antonius Laoli (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The pattern of Israelite education found in the Torah has values that can be applied in the context of education today. The pattern is a holistic approach to education, which includes moral and ethical education, respect for authority, and character development. Thus, the application of Israel's education pattern found in the Torah can help build a young generation with integrity and quality. Thus, in this study, the author or researcher uses or qualitative method approach involving in data collection and analyzing the data obtained. Overall, the Israeli education pattern is an educational system that includes the development of technical skills, the formation of student character and morals, the teaching of Jewish religion and culture, inclusive education, and the development of technological skills, all of which are designed to create competent and globally minded human resources. In conclusion, the application of Israel's pattern of education according to the Torah has also proven successful in Israel and can serve as an example for other countries in developing an effective education system. Nonetheless, it should be kept in mind that the Israeli education pattern cannot always be applied directly in other countries, due to different cultural differences and social contexts.